Thinking with Ngangas what Afro-Cuban ritual can tell us about scientific practice and vice versa - Palmié, Stephan 1959- (The University of Chicago Press, 2023)
"Inspired by the exercises of Father Lafitau, a Jesuit priest and proto-ethnographer of the "New World" who compared the lives of the Iroquois to the ancient Greeks, Stephan Palmié embarks on a series of unusual comparative investigations. What do organ transplants have to do with ngangas, a complex assemblage of mineral, animal, and vegetal materials, including human remains, that serve as the embodiment of spirits of the dead? Where do genomics and "ancestry projects" converge with divination and oracular systems? What does it mean that Black Cubans in the US took advantage of Edisonian technology to project the disembodied voice of a mystical entity named ecué onto the streets of Philadelphia? Can we consider Afro-Cuban spirit possession as an extreme form of historical knowledge production? By writing about Afro-Cuban ritual in relation to Western scientific practice, and vice versa, Palmié hopes to challenge the rationality of Western expert practices, revealing the logics that bring together enchantment and experiment. Throughout, Palmié is also levelling a specific anthropological challenge: he takes issue with the much-discussed "ontological turn," especially with those thinkers who promote notions of radical alterity and utter incommensurability. Instead, Palmié suggests that radical comparison with "boundary objects" can offer something new to the ethnographic enterprise"--
Includes bibliographical references and index
Keywords: Afroamerikanischer Synkretismus; Wissensproduktion; Naturwissenschaften; Vergleichende Forschung; Ritus; Kuba; Black people / Cuba / Religion; Anthropology of religion; Religion and science